Strategi Preservasi Tradisi Lisan Oka Masyarakat Wewewa Sumba Barat Daya - Kanisius Kami; Engel Bertha Halena Gena; Selis Ole Awa (Journal of Classroom Action Research, 2023)
This study aims to formulate a preservation strategy for the existence of the Oka oral tradition of the Wewewa community. This type of research is qualitative descriptive research. That is, to understand the strategy for preserving the Oka oral tradition of the Wewewa people, it is bound by the local wisdom values ​​contained therein. The data source for this research was obtained from the Wewewa community regarding efforts to preserve the Oka oral tradition. This research data collection technique was obtained through interviews and documentation studies. While the data analysis technique will be pursued through the stages of data transcription, data selection, data identification, data classification, and data discussion. Based on the results of the research, the researchers found a preservation strategy for the Oka oral tradition, both naturally through traditional institutions, and non-naturally through religious institutions and educational institutions.